An Intervention Using Quality of Life and Symptom Information as a Clinical Tool in Patients with Advanced Cancer - McInerney, Dr. Veronica; Mannion, Dr. Eileen; Molony, Ms. Kate; Reilly, Dr Leona; Waldron, Professor Dympna (International Journal of Innovative Research in Medical Science, 2019)
Purpose: The Schedule for Evaluation of Individual Quality of Life-Direct Weighting (SEIQoL-DW) recognizes the individuals’ values with no pre-judgement. The objective of this study was to determine if clinician awareness and understanding of individual patients’ subjective quality of life (SQoL), bothersome symptoms and symptom interference on SQoL, would lead to improvement over time in the SQoL of patients with advanced cancer. Methods: SEIQoL-DW and symptom bother/interference with SQoL was measured up to 4 time points on Sixty-five (n=65) patients receiving chemotherapy for advanced cancer. Measurements from the intervention group (n=33) was reported to the clinical team at each time point via an info-graph placed in the clinical notes. Measurements from the control group (n=32) was not reported to the clinical team. Results: SEIQoL-DW of all patients improved from baseline to time point 4 (p >0.05).A significant improvement in patient’s perception of health functioning was seen in the intervention group compared to the control group (51% v 19%, p=0.014). Symptom interference in SQoL reduced by 9% in the intervention group versus 37% increase in the control group. In totality, a 46% difference was observed between groups (p < 0.05). Interpretation: Translating SEIQoL-DW and symptom bother/interference into a format for use as a ‘Clinical Tool’ in routine practice improves patient reported health functioning and symptom interference on their SQoL. This patient centered approach could lead to a paradigm shift in our understanding of patient’s needs and in harmony with other clinical interventions, should be considered a valuable step towards personalized medicine.